GENETIC ASPECTS OF MODIFIABLE RISK FACTORS ASSOCIATED WITH ARTERIAL HYPERTENSION BY THE EXAMPLE OF THE INDIGENOUS POPULATION OF MOUNTAIN SHORIYA - T. A. Mulerova; G. V. Artamonova; M. I. Voevoda; O. V. Gruzdeva; M. Yu. Ogarkov; O. L. Barbarash (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the associations of ACE, ADRA2B, ADRB1, MTHFR and e-NOS3 candidate genes of arterial hypertension with its risk factors among the indigenous and non-indigenous population of Mountain Shoriya.Material and methods. Clinical epidemiological community-based study was conducted in hard-to-reach regions of Mountain Shoriya (villages Orton, Ust’-Kabyrza, Sheregesh in Kemerovo Region). 1178 inhabitants of the mentioned villages were examined by the continuous method, selection consisted of adult population (18 years old and above), 565 people were genotyped. All patients underwent clinical, laboratory and instrumental examination. Polymorphisms of genes ACE (I/D, rs 4340), ADRB1 (s.145A> G, Ser49Gly, rs1801252) ADRA2B (I/D, rs 28365031), MTHFR (c.677S>T, Ala222Val, rs1801133) and e-NOS3 (VNTR, 4a/4b) were tested by polymerase chain reaction.Results. Maximum number of associations with risk factors was revealed in indigenous population for genotype D/D ACE gene, in non-indigenous representatives – for genotype D/D ADRA2B gene. In indigenous carriers of genotype D/D ACE gene, the odds ratio of hypercholesterolemia, hyper-betacholesterolemia, obesity and abdominal obesity were 11.20 (р=0.018); 4.65 (р=0.001); 2.31 (р=0.031) and 1.83 (р=0.059), respectively. In the cohort of non-indigenous ethnic group in those with genotype D/D gene ADRA2B the risk of hypercholesterolemia, hyperbetacholesterolemia, hypertriglyceridemia and carbohydrate metabolism disorders was higher in 5.11 (р=0.006), 5.41 (р=0.021), 2.73 (р=0.035) and 4.13 (р=0.005) times, respectively. In the indigenous group the genotype D/D of ACE gene was associated with obesity, hypercholesterolemia, hyperbetacholesterolemia; the genotype D/D of ADRA2B gene – with hypertriglyceridemia; the genotype 4а/4а of e-NOS3 gene – with abdominal obesity. In the group of non-indigenous ethnic group genotype D/D of АСЕ gene was associated with hypoalphacholesterolemia; genotype I/I of АСЕ gene – with carbohydrate metabolism disorders; genotype D/D of ADRA2B gene – with hypercholesterolemia, hyperbetacholesterolemia and hypertriglyceridemia, carbohydrate metabolism disorders; genotype Т/Т of MTHFR gene – with hypoalphacholesterolemia, genotype C/C of MTHFR gene – with abdominal obesity.Conclusion. The determination of polymorphisms of candidate genes and the identification of associations with modifiable risk factors broadens the understanding of the genetic component of cardiovascular diseases and creates the prerequisites for the development of a more advanced and effective prevention program.